O relacjach między konserwatyzmem a faszyzmem: „Pro Fide Rege et Lege” - Stalski, Patryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article “On the relations between conservatism and Fascism: Pro Fide Rege et Lege” is a review of the recently published seventy first issue of this excellent academic periodical. The author examines the central theme of the issue and provides a synthesis of the articles published in it, especially those dealing with the conservative ideology and Fascism.
Keywords: Pro Fide Rege et Lege; konserwatyzm; faszyzm; totalitaryzm; nacjonalizm